PENGARUH QUALITY OF WORK LIFE DAN SEMANGAT KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT PLN (PERSERO) CABANG AMBON - Eline Octoviana Hutubessy (P3M Politeknik Negeri Ambon, 2023)
This research aims to determine the influence of Quality of Work Life and work enthusiasm on the work productivity of employees at PT PLN (Persero) Ambon Branch. The results of the study indicate that Quality of Work Life has a positive and significant effect on the work enthusiasm of employees at PT PLN (Persero) Ambon Branch, with a coefficient value of 0.433 or 43.3%. Furthermore, Quality of Work Life affects work productivity both directly and indirectly, where the direct impact reaches 43.30%, while the indirect impact reaches 15.42%. The total influence of the Quality of Work Life variable through work enthusiasm on the work productivity of employees is 78.90%. This signifies that Quality of Work Life has a strong influence and provides a positive contribution to the work productivity of employees at PT. PLN (Persero) Ambon Branch through work enthusiasm..Keywords: Quality of work Life, Work Enthusiasm, Work Productivity